Les rites du Mal : l’univers romanesque de Jean Genet en tant que jeu d’un péché sanctifié - Kamiński, Paweł (Romanica Silesiana)
Despite the passage of time, the literary output by Jean Genet keeps arousing controversy in both critics and readers. It is due to the contents of his works which reflect the private life of a man who is determined to separate himself from the world of “decent people” and to live among the “aristocrats of Evil”. The present study discusses the interference of various rituals that occur in Genet’s prose writing, full of villains and vagabonds. It analyses five novels: Our Lady of the Flowers, The Miracle of the Rose, Funeral Rites, Querelle of Brest and The Thief’s Journal. The main goal is to describe how those rituals are connected to one another and why Evil can be perceived as a driving force. To present a vast range of this problem, the paper takes into consideration a number of religious, erotic and criminal elements. Key words: prose works, rituals, religion, eroticism, Evil, delinquency